2004
DOI: 10.1021/es049020h
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Electron Microscopy Structural Studies of Organo-Clay Nanocomposites

Abstract: Engineering of clay nanocomposite materials by modification of their surfaces can enable the control of retention, transport, and persistence of toxic chemicals in the geosystem. The properties and interactions of clay nanocomposites have been widely studied, but little information exists on their microstructure at a range of scale extending down to atomic dimensions. The pairing of Na-montmorillonite clay with organic cations as well as with the herbicide fluridone, chosen as a model for an organic pollutant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Likewise, these values are in line with the mean platelet lengths of between 75 and 82 nm determined for a Cloisite organoclay melt compounded in nylons of medium and high molecular weights [5]. The range of platelet lengths is also consistent with the 50e400 nm diameter tactoids observed by Yaron-Marcovich et al [70] during TEM characterisation of organoclays. This basic agreement provides support for the accuracy of the platelet-length data collected for bentonite and Cloisite clays used in this work.…”
Section: Distributions Of Platelet Lengthsupporting
confidence: 90%
“…Likewise, these values are in line with the mean platelet lengths of between 75 and 82 nm determined for a Cloisite organoclay melt compounded in nylons of medium and high molecular weights [5]. The range of platelet lengths is also consistent with the 50e400 nm diameter tactoids observed by Yaron-Marcovich et al [70] during TEM characterisation of organoclays. This basic agreement provides support for the accuracy of the platelet-length data collected for bentonite and Cloisite clays used in this work.…”
Section: Distributions Of Platelet Lengthsupporting
confidence: 90%
“…The d 001 layer spacing of 14.02 Å appears to be low for NAu-2 (Keeling et al 2000). Yaron- Marcovich et al (2005) observed the layer spacing of 16 to 19 Å for HDTMA-intercalated montmorillonite (Swy-1), with the layer spacing depending on the specifi c loading of HDTMA and thus different mechanisms of its interactions with expandable clay mineral. It is possible that the layer spacing may be as low as 14.02 Å when the loading of HDTMA is lower than 60%.…”
Section: Characterization Of Cysteine-and Toluene-intercalated Nontromentioning
confidence: 99%
“…However, NanoSIMS cannot determine the morphology, elemental composition, and mineral species. High-resolution transmission electron microscopy (HRTEM) combined with selected area electron diffraction (SAED) is also a promising technique that can determine the morphology and provide detailed information on organo-mineral surfaces, as well as changes in their surface chemistries (Wen et al, 2014a;Yaron-Marcovich et al, 2005). Although direct observations of organo-mineral complexes by NanoSIMS and HRTEM have been previously described (Ramos et al, 2013;Vogel et al, 2014;Rumpel et al, 2015), few studies have reported the effects of fertilization practices on the organo-mineral complexes in soil colloids.…”
mentioning
confidence: 99%